Optimization of Monoglycerides Production Using KF/CaO-MgO Heterogeneous Catalysis - Luqman Buchori; Didi Dwi Anggoro; Indro Sumantri; Riko Rikardo Putra (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
The production of monoglyceride or monoacylglycerol (MAG) from triglycerides and glycerol has been studied. The purpose of this research was to study the effect of using KF/CaO-MgO catalyst on MAG production with batch reactor. The effect of reaction temperature, reaction time, and catalyst loading was investigated using Response Surface Methods (RSM). The reaction temperature, reaction time, and catalyst loading were varied at 200-220 ºC, 2-4 hours, and 0.1-0.3 % w/w, respectively. The maximum yield of monoglyceride 41.58% was achieved the optimum conditions of catalyst loading of 0.19 % (w/w), reaction temperature of 208.4 ºC, and reaction time of 3.20 hours.